GAMBARAN PEMBUANGAN OBAT YANG TIDAK DIGUNAKAN DI KALANGAN MASYARAKAT KOTA PALU - Nurul Ambianti; Ririen Hardani; Muhamad Rinaldhi Tandah; Handoko Putro (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Disposal of drugs that are not used in the community has a very negative impact on the environment. Many drugs are not used and become a big problem, some of which can cause contamination to the environment and disrupt the ecosystem. This study aimed to describe the description of the procurement, use, storage, disposal of drugs as well as public attitudes and information about drugs that are not used, namely damaged and expired among the people of Palu City. This study was a cross-sectional with a population of 84,374 households and a sample of 100 households in Palu City from February to April 2021. This study conducted using the convenience sampling. The independent variable in this study was drug disposal and the dependent variable was drugs that were not used. The data obtained from the questionnaire then analyzed descriptively. The result obtained that many of people bought drugs at pharmacies (78%) with reasons of wanting to buy of their own volition (38%), storing drugs in medicine boxes (56%), throwing drugs in public trash (78%) and respondents think that the improper disposal of unused and expired drugs can have an impact on the environment (70%) because many respondents have never received education related to drug disposal (65%). The majority of people throw away unused or expired drugs that they get from pharmacies in public trash and because of the lack of information regarding the disposal of drugs they get which can have a bad impact on the surrounding environment.   Keywords         : expired drug, drug disposal, unused drug